2023
DOI: 10.3390/agronomy13102541
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Seed Potato Production from In Vitro Plantlets and Microtubers through Biofertilizer Application: Investigating Effects on Plant Growth, Tuber Yield, Size, and Quality

Hiba Boubaker,
Wassim Saadaoui,
Hayriye Yildiz Dasgan
et al.

Abstract: Seed potato production often relies on mineral fertilizers. However, biofertilizers offer an eco-friendly, cost-effective means to enhance nutrient uptake, plant growth, yields, and quality while bolstering stress resilience. Two cultivars (‘Spunta’ and ‘Russet’), two in vitro materials as microtubers and plantlets, and four bio-fertilizers were used to produce seed minitubers. These bio-fertilizers included mycorrhiza (T2), microalgae (T3), beneficial bacteria (PGPR) (T4), and vermicompost (T5). Treatment T1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Consequently, this phenomenon led to the promotion of the plant growth and yield. An efficient photosynthetic organ, the increasing leaf area by the biofertilizers likely contributed to the generation of additional plant carbohydrates [31,55]. In the hydroponic cultivation of baby spinach and basil, it was reported that there were increases in leaf area when synthetic mineral fertilizers were reduced by 50% and biofertilizers were employed [23,24].…”
Section: Effects Of Biofertilizers On Plant Growth Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this phenomenon led to the promotion of the plant growth and yield. An efficient photosynthetic organ, the increasing leaf area by the biofertilizers likely contributed to the generation of additional plant carbohydrates [31,55]. In the hydroponic cultivation of baby spinach and basil, it was reported that there were increases in leaf area when synthetic mineral fertilizers were reduced by 50% and biofertilizers were employed [23,24].…”
Section: Effects Of Biofertilizers On Plant Growth Parametersmentioning
confidence: 99%
“…Naturally, bio-fertilizers consist of various strains of fungi and bacteria, intending to reduce the use of chemical fertilizers in various applications [31]. Bio-fertilizers enhance plant growth, including increasing the number of leaves, leaf area, length, shoot fresh and dry weight and root fresh and dry weight [32][33][34].…”
Section: Introductionmentioning
confidence: 99%